2022
DOI: 10.1093/pubmed/fdac042
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco and alcohol as factors for male infertility—a public health approach

Abstract: Background The study of reproductive characteristics of 430 male subjects of different age, fertility status and educational level who were involved in the program of extracorporeal fertilization at the Clinic of Gynecology and Obstetrics, Clinical Centre Niš, examined their knowledge, attitudes and behavior regarding tobacco and alcohol consumption as lifestyle risk predictors of their partial or full infertility. Methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Not only did our study demonstrate that infertility can slightly increase the risk of women developing bipolar disorder, but the MVMR analysis also found that alcoholic drinks per week appeared to reduce this risk. However, given the negative effects of alcohol on fertility, this form of relief for psychiatric disorders needs to be used with caution ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Not only did our study demonstrate that infertility can slightly increase the risk of women developing bipolar disorder, but the MVMR analysis also found that alcoholic drinks per week appeared to reduce this risk. However, given the negative effects of alcohol on fertility, this form of relief for psychiatric disorders needs to be used with caution ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the cause of male infertility has not been fully elucidated yet. Still, most of the time, it can be related to overweight, diabetes ( Service et al, 2023 ), and poor lifestyle habits such as smoking ( Sharma et al, 2016 ) and alcohol consumption ( Basic et al, 2023 ), which may impair spermatogenesis and eventually lead to the production of abnormal spermatozoa. Moreover, It was reported that more than 2% of infertile men exhibit abnormal spermatozoa ( Kumar and Singh, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can cause male infertility, mainly known as Klinefelter syndrome, varicocele, environmental or occupational exposure to toxic chemicals [4], heavy metals [5,6], smoking [7] and drinking [8], etc. Experimental and epidemiological studies show a strong connection between exposure to environmental endocrinedisrupting chemicals (EDCs) and impaired male fertility [9][10][11].…”
Section: Introductionmentioning
confidence: 99%